ACTUAL PROBLEMS OF THE THEORY OF QUALITY - V. P. Panasyuk; A. Lymar (Russian State Vocational Pedagogical University, 2016)
The aim of the publication is the analysis of the place and the role of scientific categories and application of the concept of «quality» as a threepronged science of quality, quality management, quality assessment in contemporary global processes, as well as applied aspects with regard to the adoption of specific management decisions.Methods. Methodology of interdisciplinary approach to the analysis of the "quality" category is used; the methods of theoretical analysis, synthesis and generalization.Analysis of the «quality» of the concept is carried out in conjunction with the global processes and trends in the economy, the crisis in the world, due to the emerging new technological order. The theoretical foundation that can be laid at the base of the further development of the theory of quality and making the qualitative nature of the reforms in the social sphere and the economic sphere is considered in details.Results. The tendencies, risks, problems and suggestions on the practical application of some or other quality concepts, approaches to enforcement are signified. The author's vision of the future development direction, associated with quality, including in international breaking is given.Scientific novelty consists in determining of qualitology potential applied to solve complex theoretical and practical problems, its place and role among emerging new classification of classical and non-classical sciences. The promising directions of the quality theory in relation to the economy, social sphere, education are identified.Practical significance. The proposed recommendations on use of ideas for management approaches reconsideration, organization of research and training in the field of quality.